ASSESSMENT BY MACROINVERTEBRATES OF THE ECOLOGICAL QUALITY OF SHALLOW LAKE WITH RICH SAPROPEL SEDIMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In this research, the ecological quality of the Lake Vēveru (Latvia, Rēzekne district) according to macroinvertebrates was investigated. The Lake Vēveru has a large sapropel deposit. The Lake Vēveru is relatively little affected by human economic activity, the only moderate impact is sapropel mining in the lake in 2009-2012, it is planned to resume industrial sapropel mining in the lake. During the period of sapropel removal, a decrease in the transparency of water is noted due to the nutrient flow into the water mass, pH increases, the habitat of planktonic and benthic organisms is disturbed. Macroinvertebrates samples were collected and analyzed using standard methods in the open pelagic and littoral zones of the lake in different seasons. The ecological quality of the lake was assessed in accordance with the requirements of the European Water Framework Directive in Latvia. To characterize the ecological status of the lake the Latvian Lake Macroinvertebrate Multimetric Index was used. According to the Ecological Quality Ratio (EQR) the lake indicates a good ecological status of the water. However, a moderately low species diversity index indicates the dominance of certain taxa. In general, macroinvertebrates species that are often and widely found in Latvia and are environmentally tolerant have been found in the lake. Water temperature, pH, conductivity, dissolved oxygen, oxidation reduction potential, chlorophyll-α were measured with a HACH OTT DS5 Probe. Water transparency was measured using a Secchi disc.